Measurement of the longitudinal flow-plane decorrelation using multiplane cumulants in (Formula presented.) = 200 GeV Au + Au, Ru + Ru, and Zr + Zr collisions - STAR Collaboration (Physical Review C, 2026)
Measurements of the variation of anisotropic flow-plane angles (Ψn) with rapidity, commonly known as the flow-plane decorrelation, provide important insights into the initial conditions of the matter produced in heavyion collisions. In this paper, using data collected by the STAR experiment, we report the first measurement of the four-plane correlator observable (Formula presented.), where superscripts a, b, c, and d denote sequential pseudorapidity (η) regions with a corresponding to the most backward region, b and c close to midrapidity with nb < 0 and nc > 0, and d being the most forward. The measurement is performed for the elliptic and triangular flow (i.e., n = 2 and 3) in Au + Au and isobar (Ru + Ru, Zr + Zr) collisions at (Formula presented.) = 200 GeV. The goal of calculating the correlation of the flow-plane angle variations from backward to midcentral, and from midcentral to forward regions, is to probe the systematic variation of flow angle over a wide П range. In midcentral collisions (10-30 % centrality), we find T2{ba; dc} = —0.004 ± 0.001 (stat) ± 0.002(syst) independent of the collision system. Such a small value of T2 favors a “random-walk” variation of the flow-plane angles, where the rapidity correlation length is smaller than the entire region under study. These measurements provide new information on the decorrelation patterns in the system and offer a quantitative estimate of possible systematic variations in anisotropic flow angles such as “twist” between forward and backward regions. This opens new opportunities for understanding the three-dimensional structure and the time evolution of the quarkgluon plasma created in heavy-ion collisions. © 2026 American Physical Society
Keywords: Calibration; Cumulant; Decorrelation; Noise (video); Signal processing; dept.phy